Electoral instability in Iceland 1931-95: The impact of aggregate electoral volatility and block volatility on the Icelandic party system - Pétursson, Sigtryggur (Stjórnsýslustofnun, 2005)
This article examines electoral volatility in Iceland. The impact of aggregate and block volatility on the cleavage structure of the Icelandic party system is studied and compared with the situation applying to a group of west European democracies. The Icelandic parties are divided into blocks according to their stand on the socio-economic issue dimension. This gives an opportunity to see whether the high increase in electoral volatility at the aggregate level was followed by similar increase across the cleavage line, with the party system therefore becoming less and less frozen into place, as the upsurge in electoral volatility at the aggregate level seems to suggest. The main reason for the increase in volatility across the cleavage line is traced to party splitting. The main conclusion drawn is that this has not occurred in the case of Iceland. Most of the increase in volatility has occurred within the blocks and therefore the stability of the cleavage structure of the Icelandic party system has not evidenced an overall decline.